Radiation effect on MHD ferrofluid flow with ramped wall temperature and arbitrary wall shear stress / Nor Athirah Mohd Zin ... [et al.] - Mohd Zin, Nor Athirah; Gul, Aaiza; Salleh, Siti Nur Alwani; Ullah, Imran; Mohamad Isa, Sharena; Lim, Yeou Jiann; Shafie, Sharidan (2021)
This research investigates the effect of thermal radiation on unsteady magnetohydrodynamics free convection flow of ferrofluid over a vertical flat plate with ramped wall temperature and arbitrary wall shear stress. A comparison study between the magnetic nanoparticles iron oxide (Fe2O3) and non-magnetic nanoparticles alumina oxide (Al2O3) with water-based fluid are constructed. An appropriate dimensionless variables are introduced to the governing equations and solved analytically by using the Laplace transform technique. The variations of the profile for various values of the pertinent parameters are graphically presented and discussed. The results reveal that the velocity and temperature in the ramped wall condition are always lower than in the isothermal situation. Further, the liquid with the non-magnetic nanoparticles has a higher velocity and temperature in either the ramped plate or isothermal plate.